Characterization of transients due to capacitor banks in low voltage systems - Hamad, Salih Gwami Mohammed (2017)
The scarcity of literature addressing transients due to capacitor bank switching is obvious. Hence, this study was conducted with three objectives in mind. First, to characterize capacitor bank switching transients generated in a low voltage power system with selected inductive and resistive load. During the energizing and de-energizing processes, capacitor banks generate and inject severe transient overvoltage and inrush current into the system that will result in several issues. Although there are several studies conducted on capacitor bank switching transients in medium voltage systems, there are only a few studies done on the same phenomena in low voltage systems. Previous literature shows that damage due to capacitor bank switching transients is higher in low voltage systems than that in medium and high voltage systems. Characterization of transient voltage and current in low voltage systems due to switching of capacitor banks is an important process, needed to provide solutions to the issues, which has not been done comprehensively so far. Second, to simulate the experimental power system to generate capacitor bank switching transients and validate the results with experiments. Also, it was intended to compare the simulation results by experiment in real low voltage systems in addition to calculate the specific transient energy generated by capacitor bank switching. Third, to find the response of available surge protective device in mitigating capacitor bank switching transient effects.